1976
DOI: 10.1021/bi00668a018
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a factor from Ehrlich ascites tumor cells specifically stimulating RNA polymerase II

Abstract: A factor stimulating RNA polymerase II from Ehrlich ascites tumor cells was purified. The final preparation appeared almost homogeneous on sodium dodecyl sulfate-polyacrylamide gel electrophoresis and had a molecular weight of 38 000. The endonuclease activity of about 10 mug of purified factor, if any was well below the 10(-5) mug equivalent of pancreatic deoxyribonuclease, indicating that the stimulation of RNA synthesis by this factor was not due to contaminating endonuclease. This factor specifically stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 19 publications
2
58
0
Order By: Relevance
“…Antitermination by the N protein involves the host proteins, NusA, NusB, NusG, ribosomal protein S10 and RNA elements at the 5Ј end of nascent viral transcripts. Whereas processive mechanisms found in phage have been extensively characterized and references therein), the mechanisms in eukaryotes are much less understood, except for the Drosophila hsp70 gene (Rougvie and Lis 1988;O'Brien and Lis 1991), the c-myc gene (Krumm et al 1992;Strobl and Eick 1992), and factor TFIIF (Price et al 1989;Bengal et al 1991), TFIIS (Sekimizu et al 1976), SIII (Elongin) (Bradsher et al 1993a,b;Aso et al 1995), P-TEFb (Marshall andPrice 1995;Marshall et al 1996), and HIV-1 Tat (Marciniak and Sharp 1991;Kato et al 1992;Zhou and Sharp 1995;Mancebo et al 1997;Zhu et al 1997). Tat activation of HIV-1 transcription is interesting because Tat enhances the processivity of transcription complexes in a manner reminiscent of N , and Tat activation is sensitive to DRB (Marciniak and Sharp 1991;Zhou and Sharp 1995;Mancebo et al 1997;Zhu et al 1997).…”
Section: Antitermination Mechanisms In Eukaryotesmentioning
confidence: 99%
“…Antitermination by the N protein involves the host proteins, NusA, NusB, NusG, ribosomal protein S10 and RNA elements at the 5Ј end of nascent viral transcripts. Whereas processive mechanisms found in phage have been extensively characterized and references therein), the mechanisms in eukaryotes are much less understood, except for the Drosophila hsp70 gene (Rougvie and Lis 1988;O'Brien and Lis 1991), the c-myc gene (Krumm et al 1992;Strobl and Eick 1992), and factor TFIIF (Price et al 1989;Bengal et al 1991), TFIIS (Sekimizu et al 1976), SIII (Elongin) (Bradsher et al 1993a,b;Aso et al 1995), P-TEFb (Marshall andPrice 1995;Marshall et al 1996), and HIV-1 Tat (Marciniak and Sharp 1991;Kato et al 1992;Zhou and Sharp 1995;Mancebo et al 1997;Zhu et al 1997). Tat activation of HIV-1 transcription is interesting because Tat enhances the processivity of transcription complexes in a manner reminiscent of N , and Tat activation is sensitive to DRB (Marciniak and Sharp 1991;Zhou and Sharp 1995;Mancebo et al 1997;Zhu et al 1997).…”
Section: Antitermination Mechanisms In Eukaryotesmentioning
confidence: 99%
“…TFIIS, the first eukaryotic elongation factor identified, was isolated nearly three decades ago based on its ability to induce long transcripts in an in vitro system (62). Further analysis of TFIIS revealed that it helps elongation in vitro by stimulating an RNA transcript cleavage activity of Pol II (13,23).…”
mentioning
confidence: 99%
“…Two cellular factors, TFIIF (also referred as RAP30/74, P7, and FC) (Sopta et al 1985;Conaway and Conaway 1989;Flores et al 1990;Kitajima et al 1990) and TFIIS (Sekimizu et al 1976), have been reported to enhance transcriptional elongation in vitro (Reinberg and Roeder 1987;Flores et al 1989). It was reported that TFIIS suppresses pausing and also releases the paused complex, whereas TFIIF suppresses only pausing with an increased rate of elongation (Bengal et al 1991).…”
mentioning
confidence: 99%